Cardiac penetrating injury: a rare complication associated with the lung nodule localization by hookwire - Shi, Zhe; Jin, Yuxing; Chen, Chang (Annals of Translational Medicine, 2019)
A 48-year-old woman with small lung nodule received transthoracic lung nodule localization by hookwire and subsequent lung resection. At the time of lung nodule localization, computed tomography (CT) scan showed that the localization was successful without any complication. However, cardiac penetrating injury caused by hookwire localizer was unexpectedly observed during surgery. This has occurred because the hookwire was placed too close to the anterior pulmonary vein and became inserted into left ventricle under the influence of blood flow and lung manipulation.